2007
DOI: 10.1590/s0101-20612007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade físico-química e mercado do mexilhão (Perna perna) cultivado em Ubatuba - SP

Abstract: 516Resumo O presente estudo objetivou caracterizar o mexilhão Perna perna como alimento no que se refere à estabilidade físico-química, valor nutricional e consumo. Os mexilhões avaliados foram coletados em três regiões distintas do litoral norte de São Paulo: praia da Barra Seca, praia do Engenho da Almada e costão do Cedro. Determinou-se a composição centesimal (umidade, proteína bruta, carboidrato, lipídios e cinza), o valor calórico, o pH e as bases voláteis nitrogenadas totais. Paralelamente foi realizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
1
6
1
5
Order By: Relevance
“…The moisture (74.74%) and ash (1.52%) contents detected in P. perna mussel species were lower than those found by Furlan, Galvão, Salan, and Oetterer (2007) and Cordeiro, Lopes, Oetterer, Porto, and Galvão (2007), of 83.8 and 85% for moisture and 1.8 and 3.8% for ash, respectively. Conversely, the crude protein (18.42%) and total lipids (4.07%) were higher than those verified by these same previous studies, which reported a corresponding 9.1 and 7.2% for protein and 1.1 and 1.1% for lipids, respectively.…”
Section: Centesimal Compositioncontrasting
confidence: 56%
“…The moisture (74.74%) and ash (1.52%) contents detected in P. perna mussel species were lower than those found by Furlan, Galvão, Salan, and Oetterer (2007) and Cordeiro, Lopes, Oetterer, Porto, and Galvão (2007), of 83.8 and 85% for moisture and 1.8 and 3.8% for ash, respectively. Conversely, the crude protein (18.42%) and total lipids (4.07%) were higher than those verified by these same previous studies, which reported a corresponding 9.1 and 7.2% for protein and 1.1 and 1.1% for lipids, respectively.…”
Section: Centesimal Compositioncontrasting
confidence: 56%
“…-research of mussels (Perna perna mussels) as a food product in terms of physical and chemical, food and consumer properties [6]; -assessment of histopathological monitoring of Perna perna and Itaipu Lagoon mussels [7]; -determination of the influence of different thermal processing regimes on microbiological and organoleptic parameters of Perna perna mussels [8]; -the effect of thermal and various types of preprocessing (salting, pickling) on the final characteristics of mussels meat, namely the yield of the finished product and the shelf life [9]. An integrated study of the soft body of genus Anodonta mussels is conducted to confirm the possibility of using it as a food raw material.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…7 On the other hand, in Ubatuba City (São Paulo State) it was found values significantly lower, between 0.99 to 1.49%. 20 Total lipids in mussels can seasonally vary, depending on exogenous (e.g., temperature and food availability) and endogenous (reproductive stage and energetic reserve storage) factors. 12,13 Therefore, more samplings should be performed at Ilha Grande Bay to check for any seasonal trends in the lipid contents of the mussels Perna perna.…”
Section: Total Contents Of Lipids and Pah Body Burdenmentioning
confidence: 99%